2021
DOI: 10.2478/acve-2021-0032
|View full text |Cite
|
Sign up to set email alerts
|

Key risk factors and impact of African swine fever spreading on pig production in Serbia

Abstract: African swine fever (ASF) is a viral disease of domestic pigs and wild boars and currently represents a major threat to the swine industry worldwide. Disease control is impaired by a lack of an effective vaccine and currently, it is dependent on biosecurity measures in pig production, rapid diagnosis, and stamping out of infected herds. Consequently, this swine disease has considerable social-economic significance on national or even regional level. In 2019 for the first time ASF was detected in the domestic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 42 publications
(162 reference statements)
0
25
0
Order By: Relevance
“…Disease outbreaks were registered in the next 2 months in the backyard domestic pig population. According to the epidemiological investigation, almost all cases were fi rstly detected as health disorders in sows (anorexia, abortion, death) (Polaček et al, 2021). However, the last outbreak in 2019 was confi rmed in another region, at the border with Romania in the south-east area of Vojvodina province (Petrović et al, 2021).…”
Section: Overview Of Asf Situation In Serbia (2019-2021)mentioning
confidence: 99%
See 3 more Smart Citations
“…Disease outbreaks were registered in the next 2 months in the backyard domestic pig population. According to the epidemiological investigation, almost all cases were fi rstly detected as health disorders in sows (anorexia, abortion, death) (Polaček et al, 2021). However, the last outbreak in 2019 was confi rmed in another region, at the border with Romania in the south-east area of Vojvodina province (Petrović et al, 2021).…”
Section: Overview Of Asf Situation In Serbia (2019-2021)mentioning
confidence: 99%
“…Th e distance between the fi rst and the last outbreaks was estimated to about 185-190 km. According to the results of epidemiological investigations, it was concluded that these outbreaks represent most probably two separate introductions from a neighbouring country -Romania (Polaček et al, 2021). In Europe, the long distance ASF transmission has been associated with the disposal of infected waste, meat or meat products in wild boar habitat, for example, in the Czech Republic, where the closest ASF cases were about 400-500 km away (Jurado et al, 2018;Bellini et al, 2021).…”
Section: Overview Of Asf Situation In Serbia (2019-2021)mentioning
confidence: 99%
See 2 more Smart Citations
“…The study was carried out in the period between October and December, during two consecutive hunting seasons (2013-2014) as part of a large project on pathogens occurring in wild boars. Research on the prevalence of Salmonella was supposed to continue but had to be stopped due to the outbreak of African swine fever [10]. Animals originated from twelve different hunting estates in the region of South-West Vojvodina (10 large fenced and two open areas).…”
Section: Study Area and Animalsmentioning
confidence: 99%